Cultural diplomacy and Europe's twenty years’ crisis, 1919–1939: introduction - Martin, Benjamin G.; Piller, Elisabeth (2021)
Abstract: Photographs of the German and Soviet pavilions facing off at the Paris International Exposition in 1937 offer an iconic image of the interwar period, and with good reason. This image captures the interwar period's great conflict of ideologies, the international interconnectedness of the age and the aestheticisation of political and ideological conflict in the age of mass media and mass spectacle. [Figure 1] Last but not least, it captures the importance in the 1930s of what we now call cultural diplomacy. Both pavilions – Germany's, in Albert Speer's neo-classical tower bloc crowned with a giant swastika, and the Soviet Union's, housed in Boris Iofan's forward-thrusting structure topped by Vera Mukhina's monumental sculptural group – represented the outcome of a large-scale collaboration between political leaders and architects, artists, intellectuals and graphic and industrial designers seeking to present their country to foreign visitors in a manner designed to advance the country's interests in the international arena. Each pavilion, that is, made an outreach that was diplomatic – in the sense that it sought to mediate between distinct polities – using means that were cultural – in the sense that they deployed refined aesthetic practices (like the arts and architecture) and in the sense that they highlighted the distinctive features, or ‘culture’, of a particular group (like the German nation or the Soviet state)